Corporate Bankruptcy - Donoher, William J (Business Expert Press, 2012)
Ebook from IG Library ; Corporate bankruptcy is becoming an increasingly important topic in today’s turbulent environment. The bankruptcy decision can be a matter of life and death for the organization dealing with distress, but the impact of the phenomenon is magnified by the variety of business relationships in which companies typically are involved.